Juridical Analysis of the Position of the Notary Deed That Does Not Meet the Subjective Elements as a Condition for the Validity of the Agreement - Lita Ardita Putri Widyantoro; Jawade Hafidz; Rizky Adi Prinandito (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The deed throughout 2010 recorded that 12 housing certification cases had been handled by the Notary Supervisory Council, both central and regional. It is undeniable that certain individuals can do things that violate their professional code of ethics. In conducting this research, the author uses the research method used is normative juridical literature research, the sources of which can be obtained from library materials and document studies. The result of the research is that a deed that can be canceled remains valid and binding as long as there is no court decision that has permanent legal force that cancels the deed. Legal actions as outlined in a notarial deed can be canceled if they contain juridical defects caused by several things: inability to act and disagree or disagree in making them. It is different from a deed that can be canceled because in the process of making it it does not meet the subjective elements as stated in Article 1320 paragraphs (1) and (2) of the Civil Code. As legal subjects, humans cannot be separated from things called legal actions and what humans often do in carrying out their lives is making transactions. In conducting transactions, the parties cannot agree on an agreement. The agreement according to Article 1873 of the Civil Code is a follow-up agreement made in a separate deed that is contrary to the original deed, only providing evidence between the parties but does not apply to third parties with good intentions. Based on the legal requirements of the agreement in the form of a notarial deed, the two conditions for the validity of the agreement are not fulfilled, namely the existence of an agreement to bind oneself and a lawful cause. The legal consequences can be canceled or null and void by law.